Remarkable Improvement in Foldability of Poly‐Si Thin‐Film Transistor on Polyimide Substrate Using Blue Laser Crystallization of Amorphous Si and Comparison with Conventional Poly‐Si Thin‐Film Transistor Used for Foldable Displays. Issue 5 (1st March 2020) - Do, Youngbin; Jeong, Duk Young; Lee, Suhui; Kang, Seongbok; Jang, Seonhyang; Jang, Jin
Abstract : Highly robust poly‐Si thin‐film transistor (TFT) on polyimide (PI) substrate using blue laser annealing (BLA) of amorphous silicon (a‐Si) for lateral crystallization is demonstrated. Its foldability is compared with the conventional excimer laser annealing (ELA) poly‐Si TFT on PI used for foldable displays exhibiting field‐effect mobility of 85 cm 2  (V s) −1 . The BLA poly‐Si TFT on PI exhibits the field‐effect mobility, threshold voltage ( V TH ), and subthreshold swing of 153 cm 2  (V s) −1, −2.7 V, and 0.2 V dec −1, respectively. Most important finding is the excellent foldability of BLA TFT compared with the ELA poly‐Si TFTs on PI substrates. The V TH shift of BLA poly‐Si TFT is ≈0.1 V, which is much smaller than that (≈2 V) of ELA TFT on PI upon 30 000 cycle folding. The defects are generated at the grain boundary region of ELA poly‐Si during folding. However, BLA poly‐Si has no protrusion in the poly‐Si channel and thus no defect generation during folding. This leads to excellent foldability of BLA poly‐Si on PI substrate. Abstract : By blue laser crystallization, the grain boundary can be eliminated at the thin‐film transistor (TFT) channel. This leads to excellent performance of TFT and no change in performance after folding until 30 000 cycles with radius of 2.5 mm.